2019
DOI: 10.1002/jls.21641
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Lead: Preparing Leaders of the Future through an Understanding of Role Ambiguity and Perceived Organizational Support

Abstract: The purpose of the current study was to expand on previous research on motivation to lead (MTL) by testing a situational model of MTL that included two contextual variables (i.e., goal and process clarity and perceived organizational support [POS]). Although researchers have acknowledged individual differences and situational factors may affect MTL, studies on how aspects of the work context impact an individual's MTL are limited. Thus, the current study empirically examined the effects of situational variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…New leaders' initial willingness to step into a leadership role (i.e., MTL) strengthens the relationship between power beliefs and the way new leaders behave, influenced by new leaders' perceptions of the type of leadership supported and needed by the organization. This is consistent with work adjustment theory (Dawis & Lofquist, 1984), which predicts that the congruence between individual characteristics and contextual factors (in this case, power beliefs and situational conditions) shape new leaders' behaviors, especially for those who are motivated to lead (Chan & Drasgow, 2001;Jones-Carmack, 2019).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…New leaders' initial willingness to step into a leadership role (i.e., MTL) strengthens the relationship between power beliefs and the way new leaders behave, influenced by new leaders' perceptions of the type of leadership supported and needed by the organization. This is consistent with work adjustment theory (Dawis & Lofquist, 1984), which predicts that the congruence between individual characteristics and contextual factors (in this case, power beliefs and situational conditions) shape new leaders' behaviors, especially for those who are motivated to lead (Chan & Drasgow, 2001;Jones-Carmack, 2019).…”
supporting
confidence: 85%
“…Kark and Van Dijk (2007) suggested that MTL is likely to be affected by organizational cultures that prompt promotion or prevention regulatory foci-cultures that focus on rewards and recognition compared to cultures that focus on punishing failure. Situational conditions such as pay, promotion opportunities, recognition, job design, quality of organizational communications, and workplace spirituality have been found to be related to MTL (Jones-Carmack, 2019). Perceiving support for leadership development may stimulate the new leader's motivation to reciprocate by engaging in behaviors that the organization values and rewards (Gillet et al, 2013).…”
Section: Motivation To Leadmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive understand of affective-identity motivation to lead requires an expanded model that integrates both work and non-work antecedents. As examples, both perceived organizational support and past leadership experience predict affective-identity motivation to lead (Jones-Carmack, 2019), as do prior leadership experiences in general (Bergner et al. , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences are antecedents of MTL and include personality, general cognitive ability, sociocultural values, leadership selfefficacy and past leadership experience. Recent research has sought to expand the understanding of MTL with works examining how situational factors impact and individual's MTL (Jones-Carmack, 2019). Chan and Drasgow (2001) identified three dimensions of MTL, including: affectiveidentity MTL, social-normative MTL and noncalculative MTL.…”
Section: Motivation To Leadmentioning
confidence: 99%